2023
DOI: 10.3390/ijms241512252
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Structural Dynamics of Authentic Cholesteryl Ester Transfer Protein for the Discovery of Potential Lead Compounds: A Theoretical Study

Yizhen Zhao,
Dongxiao Hao,
Yifan Zhao
et al.

Abstract: Current structural and functional investigations of cholesteryl ester transfer protein (CETP) inhibitor design are nearly entirely based on a fully active mutation (CETPMutant) constructed for protein crystallization, limiting the study of the dynamic structural features of authentic CETP involved in lipid transport under physiological conditions. In this study, we conducted comprehensive molecular dynamics (MD) simulations of both authentic CETP (CETPAuthentic) and CETPMutant. Considering the structural diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…As for the study of cholesteryl ester transfer protein (CETP), which is a promising target for mitigating cardiovascular diseases (CVD), the absence of dynamic structural characteristics under physiological conditions (authentic CETP) impedes a comprehensive understanding of the lipid transfer mechanisms and hampers the development of CETP pharmacologic inhibition. To address this, the structural differences between authentic CETP and mutant CETP (a fully active mutation used for crystal structure elucidation) were studied with the MD simulations and electron microscope (EM) data [11]. The results revealed that the authentic CETP is more flexible and conducive to the formation of a continuous tunnel in the "neck" region, providing a more favorable lipid exchange environment in contrast to the mutant CETP, thereby resulting in a greater risk of CVD.…”
Section: Molecular Insights Intomentioning
confidence: 99%
“…As for the study of cholesteryl ester transfer protein (CETP), which is a promising target for mitigating cardiovascular diseases (CVD), the absence of dynamic structural characteristics under physiological conditions (authentic CETP) impedes a comprehensive understanding of the lipid transfer mechanisms and hampers the development of CETP pharmacologic inhibition. To address this, the structural differences between authentic CETP and mutant CETP (a fully active mutation used for crystal structure elucidation) were studied with the MD simulations and electron microscope (EM) data [11]. The results revealed that the authentic CETP is more flexible and conducive to the formation of a continuous tunnel in the "neck" region, providing a more favorable lipid exchange environment in contrast to the mutant CETP, thereby resulting in a greater risk of CVD.…”
Section: Molecular Insights Intomentioning
confidence: 99%